2019
DOI: 10.1021/acs.est.9b05919
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Understanding of the Plasmid-Mediated Colistin Resistance Gene mcr-1 in Aquatic Environments

Abstract: The emergence of plasmid-mediated colistin resistance gene mcr-1 has attracted global attention and raised serious concerns about its possible cross-environment dissemination. However, the systematic exploration of mcr-1 both by monitoring and genetic dissection in aquatic environments has not been conducted. This study addresses the gap related to the occurrence and distribution of mcr-1 in watersheds, eastern China. The results showed an abundance of mcr-1 gene in four watersheds, and the highest level of mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 55 publications
3
15
0
Order By: Relevance
“…Evidence shows that the IncX4 plasmids harbouring mcr-1 genes have been recovered from human and animal E. coli isolates however, our study recovered these plasmids from the poultry environment [43]. Another study conducted in China also detected PMCR genes -mcr 1 in E. coli isolates sourced from the aquatic environment [44] however, the mcr 3.1 gene was detected in a human Salmonella case in the US [45]. This further buttresses that mcr gene has spread across multiple pathogens.…”
Section: Discussionsupporting
confidence: 58%
“…Evidence shows that the IncX4 plasmids harbouring mcr-1 genes have been recovered from human and animal E. coli isolates however, our study recovered these plasmids from the poultry environment [43]. Another study conducted in China also detected PMCR genes -mcr 1 in E. coli isolates sourced from the aquatic environment [44] however, the mcr 3.1 gene was detected in a human Salmonella case in the US [45]. This further buttresses that mcr gene has spread across multiple pathogens.…”
Section: Discussionsupporting
confidence: 58%
“…Our results indicated that mcr-1 was also prevalent in urban districts. The concentrations of mcr-1 in four samples collected from three rivers ranged from 8Á0 9 10 4 to 1Á3 9 10 7 copies per litre, which was within the range (approximately 10 3 -10 9 copies per litre) of mcr-1 in Haihe River (Yang et al 2017), Yangtze River (Wang et al 2019), and rivers in Zhejiang (Zhu et al 2020) in China. Although the drinking water source (Duong River) exhibited the lowest concentration, Day River and Nhue River were highly polluted by mcr-1 at levels of 3Á0 9 10 6 -1Á3 9 10 7 copies per litre.…”
Section: Escherichia Coli Pollution In Water Environmentsmentioning
confidence: 58%
“…The correlation between mcr-1/16S rRNA gene and intI1/16S rRNA gene was also statistically significant (r = 0Á61, P < 0Á05) (Table S2). In aquatic environments in China, a significant correlation between mcr-1 and intI1 contamination was also reported (Zhu et al 2020). In addition to mcr-1, the levels of three different ARGs (tetA, sul1, and ere(A)) were measured (Fig.…”
Section: Escherichia Coli Pollution In Water Environmentsmentioning
confidence: 64%
See 1 more Smart Citation
“…Evidence shows that the IncX4 plasmids harbouring mcr-1 genes have been detected in human and animal E. coli isolates however, our study recovered these plasmids from the poultry environment [ 43 ]. Another study conducted in China also detected PMCR genes— mcr 1 in E. coli isolates sourced from the aquatic environment [ 44 ] however, the mcr 3.1 gene was detected in a human Salmonella case in the US [ 45 ]. This further buttresses that mcr gene has spread across multiple pathogens.…”
Section: Discussionmentioning
confidence: 99%